A Group of Trusts and Combinations - Stevens, W. S. (Quarterly Journal of Economics, 1912)
I. The Electric Lamp Combination; relation to General Electrical Company, 594. — Control of tantalum and tungsten filaments, 600. — Circuit Court decree of 1911, 601. — II. The Keystone Watch Case Company, 602. — Methods of destroying competition, 607. — III. The United Shoe Machinery Company, 608. — IV. The Consolidation Coal Company; how related to Baltimore & Ohio Railroad, 613. — V. The Bath Tub Pool, 617. — Control of the jobbing trade, 623. — VI. The Cash Register Company, 625. — Deliberate destructive competition, 626. — VII. Combination of Wholesale and Retail Dealers, 630. — Michigan lumber retailers, 632. — Other lumber retailers, 634. — Wholesale lumber dealers, 637. — Pacific Coast jobbers of plumbing supplies, 640. — Southern Wholesale Grocers' Association, 641. — VIII. Conclusion, 642.